Femtosecond near-infrared laser pulses elicit generation of reactive oxygen species in mammalian cells leading to apoptosis-like death. - Tirlapur, U; König, K; Peuckert, C; Krieg, R; Halbhuber, K (2001)
Two-photon excitation-based near-infrared (NIR) laser scanning microscopy is currently emerging as a new and versatile alternative to conventional confocal laser scanning microscopy, particularly for vital cell imaging in life sciences. Although this innovative microscopy has several advantages such as highly localized excitation, higher penetration depth, reduced photobleaching and photodamage, and improved signal to noise ratio, it has, however, recently been evidenced that high-power NIR laser irradiation can drastically inhibit cell division and induce cell death. In the present study we have investigated the cellular responses of unlabeled rat kangaroo kidney epithelium (PtK2) cells to NIR femtosecond laser irradiation. We demonstrate that NIR 170-fs laser pulses operating at 80-MHz pulse repetition frequency and at mean power of > or = 7 mW evoke generation of reactive oxygen species (ROS) such as H2O2 that can be visualized in situ by standard in vivo cytochemical analysis using Ni-3,3'-diaminobenzidine (Ni-DAB) as well as with a recently developed fluorescent probe Jenchrom px blue. The formation of the Ni-DAB reaction product as well as that of Jenchrom was relatively more pronounced when irradiated cells were incubated in alkaline solution (pH 8) than in those incubated in acidic solution (pH 6), suggesting peroxisomal localization of these reaction products. Two-photon time-lapse imaging of the internalization of the cell impermeate fluorescent dye propidium iodide revealed that the integrity of the plasma membrane of NIR irradiated cells is drastically compromised. Visualization of the nuclei with DNA-specific fluorescent probes such as 4',6-diamidino-2-phenylindole 24 h postirradiation further provided tangible evidence that the nuclei of these cells undergo several deformations and eventual fragmentation. That these NIR irradiated cells die by apoptosis has been established by in situ detection of DNA strand breaks using the terminal deoxynucleotidyl transferase-mediated dUTP nick-end labeling method. Because the reactive oxygen species such as H2O2 and OH* can cause noxious effects such as cell membrane injury by peroxidation of polyunsaturated lipids and proteins and oxidative phosphorylation, and alterations of ATP-dependent Ca2+ pumps, these ROS are likely to contribute to drastic cytological alterations observed in this study following NIR irradiation. Taken together, we have established that NIR laser irradiations at mean power > or = 7 mW delivered at pulse duration time of 170 fs generally used in two- and multiphoton microscopes cause oxidative stress (1) evoking production of ROS, (2) resulting in membrane barrier dysfunction, (3) inducing structural deformations and fragmentation of the nuclei as well as DNA strand breaks, (4) leading to cell death by apoptosis.